PERCEPTION OF PSYCHOLOGICAL EFFECTS ON MALAYSIAN SEAFARERS DURING COVID-19 IN THE PERIOD OF MALAYSIA’S FIRST MOVEMENT CONTROL ORDER (MCO) - MOHD SALLEH, NURUL HAQIMIN; A RAHIM, NOOR AISYAH; JEEVAN, JAGAN; NGAH, ABDUL HAFAZ (Journal of Maritime Logistics, 2023)
The outbreak of COVID-19 might enhance the perception of psychological effects among Malaysian seafarers during the first phase of Malaysia’s Movement Control Order (MCO), often known as a "lockdown" for 6 weeks to stop the spread of coronavirus disease. According to recording data from GARD, an average of 4.6 suicide among seafarers happen each year because of mental illness. Many researchers have investigated this issue covering medical, psychological, causal factors, etc. However, limited research has been conducted on a perception of psychological effects during the first MCO that contributes to these alarming issues. Therefore, this paper attempts to identify, rank, and assess causal factors of the psychological perception state of Malaysian seafarers. Two mathematical methods will be used to achieve these objectives: An Analytic Hierarchy Process (AHP) and Evidential Reasoning (ER). An AHP is used to rank each identified perception of psychological effect on Malaysian seafarers. Then an ER is applied to assess the perception of psychological impact and synthesize the subset. The result has shown the most critical effect for a perception of psychological effects among Malaysian seafarers is depression disorder (0.6658), followed by anxiety disorder (0.5216) and stress (0.5122). Half of the respondent agreed on their perception of psychological effect during the first phase of movement control order with 0.5863. This research is expected to benefit the researcher, seafarers, experts in psychology fields, and even the people who have a problem in psychology in profoundly understanding the causal factors of psychology among Malaysian seafarers.